IL-4Rα Signaling in Keratinocytes and Early IL-4 Production Are Dispensable for Generating a Curative T Helper 1 Response in Leishmania major-Infected C57BL/6 Mice - Descatoire, Marc; Hurrell, Benjamin P.; Govender, Melissa; Passelli, Katiuska; Martinez-Salazar, Berenice; Hurdayal, Ramona; Brombacher, Frank; Guler, Reto; Tacchini-Cottier, Fabienne (Frontiers in Immunology, 2017)
Experimental infection with the protozoan parasite Leishmania major has been extensively used to understand the mechanisms involved in T helper cell differentiation. Following infection, C57BL/6 mice develop a small self-healing cutaneous lesion and they are able to control parasite burden, a process linked to the development of T helper (Th) 1 cells. The local presence of IL-12 has been reported to be critical in driving Th1 cell differentiation. In addition, the early secretion of IL-4 was reported to potentially contribute to Th1 cell differentiation. Following infection with L. major, early keratinocyte-derived IL-4 was suggested to contribute to Th1 cell differentiation. To investigate a putative autocrine role of IL-4 signaling on keratinocytes at the site of infection, we generated C57BL/6 mice deficient for IL-4Rα expression selectively in keratinocytes. Upon infection with L. major, these mice could control their inflammatory lesion and parasite load correlating with the development of Th1 effector cells. These data demonstrate that IL-4 signaling on keratinocytes does not contribute to Th1 cell differentiation. To further investigate the source of IL-4 in the skin during the first days after L. major infection, we used C57BL/6 IL-4 reporter mice allowing the visualization of IL-4 mRNA expression and protein production. These mice were infected with L. major. During the first 3 days after infection, skin IL-4 mRNA expression was observed selectively in mast cells. However, no IL-4 protein production was detectable locally. In addition, early IL-4 blockade locally had no impact on subsequent Th1 cell differentiation and control of the disease. Taken together, the present data rule out a major role for skin IL-4 and keratinocyte IL-4Rα signaling in the development of a Th1 protective immune response following experimental infection with L. major.